Panax Notoginseng Saponins Restrains Ischemia-reperfusion-induced Rat Mesenteric Microcirculatory Disturbance - Yu Zhang; Yu-Ying Liu; Quan Li; Chun-Shui Pan; Jing-Yu Fan; Chuan-She Wang; Kai Sun; Jing-Yan Han (World Journal of Traditional Chinese Medicine, 2015)
Objective: To investigate the effect of Panax notoginseng saponins (PNS) on ischemia reperfusion (I/R) induced rat mesenteric microcirculatory dysfunctions.